2022
DOI: 10.3390/cells11244105
|View full text |Cite
|
Sign up to set email alerts
|

To Be or Not to Be? Are Reactive Oxygen Species, Antioxidants, and Stress Signalling Universal Determinants of Life or Death?

Abstract: In the environmental and organism context, oxidative stress is complex and unavoidable. Organisms simultaneously cope with a various combination of stress factors in natural conditions. For example, excess light stress is accompanied by UV stress, heat shock stress, and/or water stress. Reactive oxygen species (ROS) and antioxidant molecules, coordinated by electrical signalling (ES), are an integral part of the stress signalling network in cells and organisms. They together regulate gene expression to redirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 191 publications
(350 reference statements)
1
23
0
Order By: Relevance
“…Numerous studies have shown that SOD activity markedly increases when plants encounter various abiotic stresses, such as high light, drought, and metal toxicity. SOD activity is often positively correlated with plant tolerance against environmental stress (Szechyńska-Hebda et al, 2022a).…”
Section: Superoxide Dismutasementioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies have shown that SOD activity markedly increases when plants encounter various abiotic stresses, such as high light, drought, and metal toxicity. SOD activity is often positively correlated with plant tolerance against environmental stress (Szechyńska-Hebda et al, 2022a).…”
Section: Superoxide Dismutasementioning
confidence: 99%
“…The resulting damage has negative effects on plant growth, development, and ultimately survival. Thus, maintaining a balance between the generation and detoxification of ROS is vital for normal cellular functions (Szechyńska-Hebda et al, 2022a).…”
Section: Ros Metabolismmentioning
confidence: 99%
See 3 more Smart Citations